Analisis Praktik Klinik Keperawatan Pada Pasien CKD (Chronic Kidney Disease) Dengan Intervensi Inovasi Sipping Ice Cube Therapy Terhadap Penurunan Rasa Haus Di Ruang Perawatan Rsud. Prof. DR. H. Aloei Saboe Kota Gorontalo - Fadli Syamsuddin; Iskandar Simbala; Hendra Radjulani (Lembaga Pengembangan Kinerja Dosen, 2023)
Chronic Kidney Disease (CKD) This is a gradual and irreversible kidney disorder that affects the body's capacity to regulate metabolism, fluids, and electrolytes, leading to the development of uremia. Hemodialysis (HD) patients with chronic renal failure are subject to fluid, dietary and pharmaceutical restrictions as well as activity and medication limits. Weight gain, edema, and high blood pressure will occur if fluid balance is not maintained or if there is excess fluid between dialysis sessions. But limiting fluids while receiving hemodialysis can have a number of negative consequences on the body, one of which is thirst and dry mouth (xerostomia), caused by decreased salivary gland production. This scientific study uses a descriptive methodology along with nursing care strategies to apply the